Singapore’s Nascent Urban Farming : Potential Future Regional Centre? - Montesclaros, Jose Ma. Luis P. (2018)
Singapore signalled strong support for its urban farming industry by tendering 24 hectares of land for high-productivity vegetable farms in 2017. Foresighted action is now needed to reduce risk to leafy vegetable producers and to fulfil the sector’s commercial potential. Can it be a future regional centre for urban food production?